2017
DOI: 10.1007/s12017-017-8469-3
|View full text |Cite
|
Sign up to set email alerts
|

(E)-2-Methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) Phenol Ameliorates LPS-Mediated Memory Impairment by Inhibition of STAT3 Pathway

Abstract: Alzheimer’s disease (AD) is pathologically characterized by an excessive accumulation of amyloid-beta (Aβ) fibrils within the brain. We tested the anti-inflammatory and anti-amyloidogenic effects of (E)-2-methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) phenol (MMPP), a selective signal transducer and activator of transcription 3 (STAT3) inhibitor. We examined whether MMPP (5 mg/kg in drinking water for 1 month) prevents amyloidogenesis and cognitive impairment on AD model mice induced by intraperitoneal LPS (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…In our study, MMPP inhibited STAT3 DNA binding and transcriptional activity, suggesting that MMPP can inhibit neuroinflammation through inactivation of astrocytes via blocking STAT3-mediated p38 and JNK MAPK pathways. Previously, we reported that MMPP has anti-inflammatory effects in inflammatory disease models such as AD, rheumatoid arthritis, and cancer [29,49,50]. We did not detect any side effects of MMPP with the effective dose of MMPP (5 mg/kg) during treatment for 30 days [29].…”
Section: Discussionmentioning
confidence: 65%
“…In our study, MMPP inhibited STAT3 DNA binding and transcriptional activity, suggesting that MMPP can inhibit neuroinflammation through inactivation of astrocytes via blocking STAT3-mediated p38 and JNK MAPK pathways. Previously, we reported that MMPP has anti-inflammatory effects in inflammatory disease models such as AD, rheumatoid arthritis, and cancer [29,49,50]. We did not detect any side effects of MMPP with the effective dose of MMPP (5 mg/kg) during treatment for 30 days [29].…”
Section: Discussionmentioning
confidence: 65%
“…In addition, these substances could reduce the population of activated microglia and astrocytes by inhibiting the STAT3 signaling pathway and could exert anti-neuroinflammatory effects [48, 49]. These substances simultaneously inhibited Aβ accumulation, thereby alleviating memory impairment raising the possibility of treating AD [48, 50]. As an example, we have demonstrated that (E)-2-methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) phenol inhibits the STAT3 signaling pathway, alleviates neuroinflammation, inhibits Aβ accumulation, and eventually restores memory impairment and cognitive abilities in an AD mouse model [50].…”
Section: Discussionmentioning
confidence: 99%
“…These substances simultaneously inhibited Aβ accumulation, thereby alleviating memory impairment raising the possibility of treating AD [48, 50]. As an example, we have demonstrated that (E)-2-methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) phenol inhibits the STAT3 signaling pathway, alleviates neuroinflammation, inhibits Aβ accumulation, and eventually restores memory impairment and cognitive abilities in an AD mouse model [50]. Eufumi et al demonstrated that proinflammatory cytokines such as IL-6 induce phosphorylation of STAT3 and that phosphorylated STAT3 continues to activate microglia [18].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation in AD can be induced by exogenous pathogens and sterile endogenous agents (Ishida et al, 2017[ 7 ]). LPS, an endotoxin isolated from gram-negative bacteria, can induce inflammatory responses, amyloidogenesis and neuronal damage, thus accelerating the progression of a neurodegenerative disease (Choi et al, 2017[ 1 ]). LPS has been widely used to conduct an experimental model of microglia activation (Choi et al, 2017[ 1 ]).…”
Section: Discussionmentioning
confidence: 99%
“…LPS, an endotoxin isolated from gram-negative bacteria, can induce inflammatory responses, amyloidogenesis and neuronal damage, thus accelerating the progression of a neurodegenerative disease (Choi et al, 2017[ 1 ]). LPS has been widely used to conduct an experimental model of microglia activation (Choi et al, 2017[ 1 ]). LPS administered into brain induces microglia activation, and results in accumulation of Aβs in both the cerebral cortex and hippocampus (Sheng et al, 2013[ 17 ]).…”
Section: Discussionmentioning
confidence: 99%